Adsorption isotherms and thermodynamic properties of Carthamus tinctorius L. seeds - Jaqueline F. V. Bessa; Osvaldo Resende; Daniel E. C. de Oliveira; Rayr R. de Lima; Wellytton D. Quequeto; Valdiney C. Siqueira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Safflower is a crop of high economic value with high oil concentration in its seeds and great industrial versatility, besides various benefits to human health. As with other agricultural crops, it is common to store safflower to make it available in different periods of the year and, due to its hygroscopic characteristics, studies evaluating the effect of temperature and air relative humidity on its moisture content become relevant. Thus, the objective of the present study was to determine the water adsorption isotherms of safflower seeds and analyze their thermodynamic properties. Moisture contents of 6.5, 6.9, 7.3, 7.7, 8.3 and 9.1% (dry basis) were obtained by adsorption under controlled conditions of temperature (30 °C) and relative air humidity (90%). The adsorption isotherms were obtained by the indirect static method at different temperatures (10, 20, 30 and 40 °C). As temperature increased, for the same moisture content, there was an increase in water activity and, for constant water activity, the values of equilibrium moisture content decreased with increasing temperature. Chung-Pfost model showed the best fit to describe the phenomenon of hygroscopicity of safflower seeds. The thermodynamic properties were influenced by the moisture content of the seeds, reducing the energy necessary for water absorption in the product with the increase in adsorption, and the enthalpy-entropy theory was controlled by enthalpy.